2013
DOI: 10.1007/978-3-642-38833-0_16
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of IT Service Management Process Improvement Initiatives: A Case Study Approach

Abstract: Abstract. IT companies worldwide have started to improve their service management processes based on best practice frameworks, such as IT Infrastructure Library (ITIL). However, many of these companies face difficulties in demonstrating the positive outcomes of IT service management (ITSM) process improvement. This has led us to investigate the research problem: What positive impacts have resulted from IT service management process improvement? The main contributions of this paper are 1) to identify the ITSM p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
(10 reference statements)
2
3
0
Order By: Relevance
“…The challenges reported are consistent with those found in prior studies on ITIL implementation: difficulties in measuring and reporting ITSM outcomes (Gacenga, CaterSteel, & Toleman, 2010); the importance of process integration (Beath & Straub, 1989;Shang & Shu-Fang, 2010); proactive orientation to incident management (Järveläinen, 2013); classification of incidents and service requests as well as identification of problems (Jantti, Rout, Wen, Heikkimen, & Cater-Steel, 2013). Our findings also confirm the view of Niessink and van Vliet (2000) that IT support organizations experience issues at the interface between incident management and problem management.…”
Section: Figure 2 Challenging Areas In Service Operationsupporting
confidence: 88%
“…The challenges reported are consistent with those found in prior studies on ITIL implementation: difficulties in measuring and reporting ITSM outcomes (Gacenga, CaterSteel, & Toleman, 2010); the importance of process integration (Beath & Straub, 1989;Shang & Shu-Fang, 2010); proactive orientation to incident management (Järveläinen, 2013); classification of incidents and service requests as well as identification of problems (Jantti, Rout, Wen, Heikkimen, & Cater-Steel, 2013). Our findings also confirm the view of Niessink and van Vliet (2000) that IT support organizations experience issues at the interface between incident management and problem management.…”
Section: Figure 2 Challenging Areas In Service Operationsupporting
confidence: 88%
“…Therefore, consistent with previous studies [18,19], this study found that improving processes results in higher process capability attainment, as evident by a reduction in the number of recommendations for improvement.…”
Section: Summary Of Process Improvementsupporting
confidence: 91%
“…Service Management automation as a driver of IT industrialization has been a subject of great expectation and optimistic prediction [9]. Some of the benefits of the IT Service Management initiative perceived by the organization are customer satisfaction, staff satisfaction, service management culture, better process maturity/more standard process, improved tools and technology, improved service standard, improved service quality, improved efficiency/productivity, cost reduction, and better operational transparency [10]. ITSM frameworks can provide numerous organizational benefits when implemented in a planned and "conscious" manner [7], such as:…”
Section: Introductionmentioning
confidence: 99%